Implementasi Inovasi Sistem Layanan Nomor Tunggal Panggilan Darurat 112 dalam Meningkatkan Pelayanan Publik Dinas Komunikasi dan Informasi Kota Pekanbaru - Kelvin Chandra; Ahmad Hadi (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
Public service is a government responsibility that must be continuously improved in line with evolving community needs. One form of innovation is the Single Emergency Call Number (NTPD) 112, which connects the public with the regional emergency service center. In the city of Pekanbaru, this service has been implemented by the Department of Communication and Information Technology to facilitate public complaints, in accordance with Ministry of Communication and Information Technology Regulation No. 10 of 2016. This study employs a qualitative descriptive method and involves department officials and the public as subjects. The results indicate that the NTPD 112 program has not yet been successful, but it still faces several challenges, such as insufficient public awareness, low public understanding of the service features, and inadequate operator response. The government is striving to improve education and services related to disaster management. However, public awareness of the importance of emergency services remains low, resulting in the program's effectiveness not yet being optimal in reducing disaster risks.